Resentment and retrenchment: Rereading Doniger on comparison and Edward Said - Geslani, Marko (Religion compass, 2021)
Despite significant genealogical work in recent decades, curricula in religious studies still struggle to incorporate disciplinary histories of colonialism and Orientalism, especially at the undergraduate level. This reticence seems ironic, given the historic importance of Asian religions to twentieth century frameworks of comparison still regnant today. To assess this postcolonial impasse, I juxtapose Wendy Doniger's theory of comparison in her 1998 work, The Implied Spider, to her obliquely critical comments on Edward Said and postcolonial studies. Doniger's still canonical work illustrates a tendency to post-Saidian retrenchment, which poses postcolonial thought beyond the bounds of the humanism that undergirds the comparative approach to religious studies. To the extent that such deferrals of postcolonial politics continue to hold sway, they will inhibit our development of antiracist pedagogies in the field.